Continuous Spike and Wave in Slow-Wave Sleep in a Patient With Rett Syndrome and in a Patient With Lhermitte-Duclos Syndrome and Neurofibromatosis 1. (December 2014) - Bhat, Sushanth; Ming, Xue; Dekermenjian, Rony; Chokroverty, Sudhansu
Continuous spike and wave in slow-wave sleep (CSWS) is an electroencephalographic (EEG) pattern characterized by generalized spike-wave discharges occurring for at least 85% of non–rapid eye movement (non-REM) sleep, with marked attenuation during rapid eye movement (REM) sleep. It has been described in a large number of structural and nonstructural neurologic conditions and is associated with epilepsy, behavioral disturbances, and severe neuropsychiatric impairment. We describe continuous spike and wave in slow-wave sleep in 2 patients (one with Rett syndrome and the other with Lhermitte-Duclos syndrome). To our knowledge, continuous spike and wave in slow-wave sleep has not been previously described in these conditions.